Do Financial Systems Spur Economic Growth in the USA? An Empirical Investigation - Nyasha, Sheilla; Odhiambo, Nicholas M. (Panoeconomicus, 2018)
In this paper, we use the autoregressive distributed lag (ARDL) bounds testing approach to examine the dynamic impact of both bank-based financial development and market-based financial development on economic growth in the United States of America (USA) during the period 1980 to 2012. In order to adequately capture the depth and width of the USA’s financial system, we used both bank-based and market-based financial development indices as proxies for bank-based and market-based financial systems. These indices were constructed from a number of bank- and market-based financial development indicators, using the method of means-removed average. Our empirical results reveal that both bank-based and market-based financial development have a positive impact on economic growth in the USA. These results apply irrespective of whether the regression analysis is conducted in the long run or in the short run. We, therefore, recommend that both pro-bank-based and pro-market-based financial sector development policies should be pursued in the USA - in order to bolster real sector growth and economic development. Key words: United States of America, USA, Bank-based financial development, Market-based financial development, Economic growth. JEL: G10, G20, O16. Da li finansijski sistemi podstiču ekonomski rast SAD? Empirijska analiza U ovom radu koristimo pristup testiranja granica autoregresivnog modela sa distributivnim vremenskim pomakom (ARDL) kako bismo ispitali dinamički uticaj finansijskog razvoja zasnovanog na bankama i tržišno zasnovanog finansijskog razvoja na ekonomski rast u Sjedinjenim Američkim Državama (SAD) u periodu od 1980. do 2012. godine. Da bi se na adekvatan način obuhvatila dubina i širina finansijskog sistema SAD, koristili smo i bankarske i tržišno zasnovane finansijske indekse razvoja kao pokazatelje za bankarske i tržišne finansijske sisteme. Ovi indeksi su konstruisani iz niza indikatora finansijskog razvoja zasnovanog na bankama i tržišno zasnovanog finansijskog razvoja, koristeći metodu proseka pokretnih sredina. Naši empirijski rezultati pokazuju da i bankarski i tržišno zasnovani finansijski razvoj pozitivno utiču na ekonomski rast SAD. Ovi rezultati se primenjuju bez obzira na to da li se regresiona analiza sprovodi u dugom ili u kratkom roku. Stoga, preporučujemo da se u SAD primene kako politike razvoja finansijskog sektora koje se zasnivaju bankama, tako i politike razvoja finansijskog sistema koje se zasnivaju na tržištima - u cilju jačanja rasta realnog sektora i ekonomskog razvoja. Ključne reči: SAD, finansijski razvoj zasnovan na bankama, finansijski razvoj zasnovan na tržištu, ekonomski rast.